The Bleeding Vale - Basharat Ali Syed (Rawalpindi Atiq Publishing House, 1991)
On the atrocities of the Indian army in Jammu and Kashmir.
Include Illustrations and Appendix.
Keywords: Political atrocities -- India--Jammu and Kashmir -- Politics and government